X-ray diffraction mineralogy of sediment core MD99-2323 - John T Andrews (PANGAEA, 2021)
Weight % of non-clay and clay minerals based on quantitative X-ray diffraction using the “whole-pattern” Rockjock v6.0 Excel macro program (calibrated with 10% zincite) (Eberl, 2003). Data calculated to sum to 100%.